AabHLH113 integrates jasmonic acid and abscisic acid signaling to positively regulate artemisinin biosynthesis in Artemisia annua. Issue 3 (1st December 2022) - Yuan, Mingyuan; Shu, Guoping; Zhou, Jiaheng; He, Ping; Xiang, Lien; Yang, Chunxian; Chen, Ming; Liao, Zhihua; Zhang, Fangyuan
Summary: Artemisinin, a sesquiterpene lactone isolated from Artemisia annua, is in huge market demand due to its efficient antimalarial action, especially after the COVID‐19 pandemic. Many researchers have elucidated that phytohormones jasmonic acid (JA) and abscisic acid (ABA) positively regulate artemisinin biosynthesis via types of transcription factors (TFs). However, the crosstalk between JA and ABA in regulating artemisinin biosynthesis remains unclear. Here, we identified a novel ABA‐ and JA‐induced bHLH TF, AabHLH113, which positively regulated artemisinin biosynthesis by directly binding to the promoters of artemisinin biosynthetic genes, DBR2 and ALDH1 . The contents of artemisinin and dihydroartemisinic acid increased by 1.71‐ to 2.06‐fold and 1.47‐ to 2.23‐fold, respectively, in AabHLH1113 overexpressed A. annua, whereas they decreased by 14–36% and 26–53%, respectively, in RNAi‐ AabHLH113 plants. Furthermore, we demonstrated that AabZIP1 and AabHLH112, which, respectively, participate in ABA and JA signaling pathway to regulate artemisinin biosynthesis, directly bind to and activate the promoter of AabHLH113 . Collectively, we revealed a complex network in which AabHLH113 plays a key interrelational role to integrate ABA‐ and JA‐mediated regulation of artemisinin biosynthesis.